Construction of dual-function carbon materials network towards high performance MnCO3 anode via nanoprecipitation process. (20th October 2020) - Tang, Yanqing; Xi, Yuming; Lu, Yangcheng
Highlights: Developed a facile method for preparing hybrids of MnCO3 and carbon additives. Achieved one-step construction of conductive network for MnCO3 anode. Revealed dual-function of compound carbon additives for electrochemical performance enhancement. Afforded excellent cycling and rate performance for MnCO3 with low carbon content. Abstract: We established a simple aqueous precipitation platform assisted with ethanol for preparing MnCO3 and carbon materials composite. After revealing the structure-function relationship between the structure and its electrochemical performance by exploring the effects of different variables during the synthetic process, we proposed a one-step strategy and directly synthesize composite without adding extra carbon additives while preparing the electrode. Such a hybrid with a dual-function networks possesses both inside and outside conductive networks, which intensively improves conductivity and the activation process towards the top capacity. Moreover, the inside conductive network could play a role as a framework of the MnCO3 and improve the cyclic performance. As a result, the well-designed hybrid structure could reach a high reversible capacity of 860 mAh g −1 at a 1 C rate with a high capacity-retention of 82.5% after 500 cycles. Even at 5 C rate, the top discharge capacity is capable of maintaining 611.3 mA h g −1 with the capacity-retention up to 95.5% after 500 cycles. This strategy provides a facile and reliable path for integrating carbon additives and MnCO3 as a promising anode for lithium-ion batteries, which can also be applied to other electrochemical materials suffering from large volume changes or low conductivity. Graphical abstract: Image, graphical abstract